Examining the evolution of gaming and its impact on social, cultural, and political perspectives - Valentine, Keri Duncan; Jensen, Lucas John (Advances in human and social aspects of technology book series, 2016)
"This book asks whether video games have the power to transform a player and his or her beliefs from a sociopolitical perspective, allowing users to immerse themselves in new worlds, situations, and politics"--Provided by publisher